Effect of BEMER signal on biological restitution and cognitive processes after endurance exercise. A case study - Mirosław Mrozkowiak; Magdalena Mrozkowiak; Hanna Zukowska; Marek Sokołowski (Kazimierz Wielki University, 2016)
Mrozkowiak Mirosław, Mrozkowiak Magdalena, Zukowska Hanna, Sokołowski Marek. Effect of BEMER signal on biological restitution and cognitive processes after endurance exercise. A case study. Journal of Education, Health and Sport. 2016;6(10):175-196. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160628 http://ojs.ukw.edu.pl/index.php/johs/article/view/3932       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 12.10.2016.       Effect of BEMER signal on biological restitution and cognitive processes after endurance exercise. A case study   Mirosław Mrozkowiak2, Magdalena Mrozkowiak2, Hanna Zukowska1, Marek Sokołowski3   1Kazimierz Wielki University in Bydgoszcz, Department of Physical Education, Health and Tourism 2Bioergonsport, Nowa Biała 8p, 09-411 Biała, Polska 3Academy of Physical Education, Poznań     Summary             Capillary network density in particular tissues grows proportionally to their oxygen demand. BEMER therapy, used as complex or supplementary treatment, improves basic physiological processes, angiokinesis, microcirculation, as well as oxygenation and nutrition of muscle cells. Material and methods. The study was conducted on a male individual who leads a healthy life style and who twice subjected himself to the markings of cognitive functions and selected blood indicators; first, during natural physiological restitution after endurance effort, and second, after restitution enhanced with BEMER therapy.  Results. Most significant changes after endurance effort were observed in the following blood indicators: leukocytes, erythrocytes, insulin and cortisol. Least significant changes were noted in the number of lymphocytes and in cognitive functions. Conclusion. •  Applied methodology and profile of BEMER signal, through increasing the lumen of microcirculation vessels, variously affects the value of selected blood indicators • The individual results achieved from the conducted measurements may not serve a basis for drawing generalized conclusions on after-endurance effect of BEMER signal; instead, they may be treated as an attempt at showing a direction for further research on the possible changes in the application method of the structurally multidimensional BEMER signal as well as on the intensification of biological restitution after various physical efforts. • More beneficial results of TMT test observed in the second course of measurements are rather a result of learning process than of BEMER therapy itself.